Aprovechamiento de Residuos de Construcción y Demolición (RCD) y residuos de hojas de maíz en la fabricación de eco-concretos. Caso de estudio Neiva - Ramos Páez, María Paula (Universidad Antonio Nariño, 2022)
In order to seek alternative utilization to mitigate negative impacts generated by the extraction of raw materials in the preparation of concrete and the inappropriate final disposal of the RCD in the city of Neiva-Colombia, the natural aggregates that make up conventional concrete are obtained. (cement-gravel-sand), in addition to recycled materials such as: concrete waste in coarse (3/8 ”) and fine (8”) granulometries, as well as excavation sand waste and corn husk waste, destined to be Characterized granulometrically and physico-chemically for comparative purposes and afterwards, elaborate eleven eco-concretes and two eco-mortars with different percentages of recycled material ranging from 10% to 75% replacement